Leading change in financial service organisations: An exploration of employees' perceptions of management of change using an organisational justice framework - Constantinos Choromides (SPOUDAI - Journal of Economics and Business, 2021)
Change is accepted as a process determined among an organisation's senior management; therefore, employees would predominately resist the change process, making it necessary for change strategists to address the resistance prior to implementing the change programme. Since a strategic challenge in any major organisational change is the ability to manage different responses to change among employees, this article's novelty and practical contribution is in using the concept of organisational justice framework to explore and understand the awareness, perceptions and responses of the employees, irrespective of their level in the organisational hierarchy, around the change management approaches and processes; offering valuable insights into our knowledge on how employees' respond to change and the effect that their responses has on any change programme. Using data, from an in depth case study, from 6 senior managers, and 33 staff members selected through purposive sample, we identify numerous key challenges that need to be considered and resolved to enable financial services organisations to design successful change strategies. Using a qualitative research design and moving away from the methodology employed in previous research where participants reported only on predetermined questions via structured questionnaires focusing on the positive or negative aspects of change, we employed an interview questionnaire that allowed participants to choose for themselves which characteristics of the change experience they will consider, thus exploring the employees' diverse perceptions of organisational change. Key findings from this study suggest that organisational justice can act not only as an indicator for the effective execution of the change initiatives, but also as a framework for understanding employees' perceptions of management of change, and enable effective change strategy development in the organisational environment. Other important findings suggest that organisational justice can be used to forecast employee reactions and behaviours around the desired change and incorporate strategies and procedures that will successfully facilitate change p rocess in the future. Finally, the study contributes to existing knowledge around organisational justice literature within the context of management of change.
Keywords: J5; M1; M5; 330; change management; change process; organisational justice; organisational change perceptions